Assessing preparation for care transition among adolescents with rheumatologic disease: a single-center assessment with patient survey - Jordan E. Roberts; Olha Halyabar; Carter R. Petty; Mary Beth Son (BMC, 2021)
Abstract Background Despite the risk for poor outcomes and gaps in care in the transfer from pediatric to adult care, most pediatric rheumatology centers lack formal transition pathways. As a first step in designing a pathway, we evaluated preparation for transition in a single-center cohort of adolescents and young adults (AYA) with rheumatologic conditions using the ADolescent Assessment of Preparation for Transition (ADAPT) survey. Findings AYA most frequently endorsed receiving counseling on taking charge of their health and remembering to take medications. Less than half reported receiving specific counseling about transferring to an adult provider. AYA with lower education attainment compared with those who had attended some college or higher had lower scores in self-management (1.51 vs 2.52, p = 0.0002), prescription medication counseling (1.96 vs 2.41, p = 0.029), and transfer planning (0.27 vs 1.62, p < 0.001). AYA with a diagnosis of MCTD, Sjögren's or SLE had higher self-management scores than those with other diagnoses (2.6 vs 1.9; p = 0.048). Non-white youth indicated receiving more thorough medication counseling than white youth (2.71 vs 2.07, p = 0.027). When adjusting for age, educational attainment remained an independent predictor of transfer planning (p = 0.037). AYA with longer duration of seeing their physician had higher transition preparation scores (p = 0.021). Conclusion Few AYA endorsed receiving comprehensive transition counseling, including discussion of transfer planning. Those who were younger and with lower levels of education had lower preparation scores. A long-term relationship with providers was associated with higher scores. Further research, including longitudinal assessment of transition preparation, is needed to evaluate effective processes to assist vulnerable populations.